The mediating role of self-acceptance in the relationship between loneliness and subjective well-being among the elderly in nursing home: A cross-sectional study. Issue 40 (8th October 2021) - Li, Shanshan; Zhang, Xing; Luo, Caifeng; Chen, Moyan; Xie, Xin; Gong, Fuyu; Lv, Fei; Xu, Jianou; Han, Juan; Fu, Lin; Sun, Yanpeng
Abstract : Abstract: The purpose of this study was to investigate the mediating effects of self-acceptance on loneliness and subjective well-being (SWB) among elderly subjects living in Chinese nursing homes. This cross-sectional study was conducted between October 2019 and March 2020. A total of 415 elderly participants aged 60 to 97 years (mean 81.12 ± 8.90 years) from 3 medical and nursing homes in Fuyang city, Anhui province, were selected using a convenience sampling method. Data were collected using a general information questionnaire, the Memorial University of Newfoundland Scale of Happiness, the self-acceptance scale, and the UCLA Loneliness scale. Correlations, regressions, and structural equation models were used for the analyses. Multiple linear regression analysis was performed to confirm the factors influencing the SWB. Bootstrapping was performed to confirm the mediation effect. The loneliness of elderly subjects in nursing homes was significantly correlated with self-acceptance and SWB ( r = −0.338, P < .01; r = −0.383, P < .01), and self-acceptance was significantly correlated with SWB ( r = 0.401, P < .01). Multiple linear regression revealed that the relationship with children, loneliness, residence time in nursing homes, income, marital status, self-acceptance, original residence, and frequency of children's visits were the main factors affecting SWB. Bootstrapping showed that the mediating role of self-acceptance was statistically significant. The SWB of elderly individuals living in Chinese nursing homes was moderate. Low-income people, subjects from rural areas, and those newly admitted to nursing homes should be emphasized in interventions, and appropriate measures should be taken to harmonize the relationships between elderly residents and their children. Self-acceptance partially mediated the relationship between loneliness and SWB. Consequently, self-acceptance should be the focus of improving the SWB of elderly nursing home residents.